Diagnosis Organisasi Pengembangan Pusat Informasi dan Konseling Remaja dan Mahasiswa di Kabupaten Pati - Wijanarko Wijanarko; Nina Widowati; Slamet Santoso (Journal of Public Policy and Management Review, 2014)
The organization can be described as an open system, meaning that organization alive and brought to life by their surrounding environment, both external and internal of the organization. Therefore organizations must be able to adapt to their environment by development organization. The Diagnosis of an organization is how to detect and find basic problems faced by the organization. This research aims to know the main problem faced by the PIK R/M in Pati Regency through organizational diagnosis survey method with the Weishbord Model Six Boxes approach. And then determine the pattern of intervention that allows for the development of the Organization are applied in PIK R/M Pati Regency. Six boxes of weishbord was diagnose the organization through six boxes of the variables the purpose, structure, relationships, rewards, leadership, and helpful mechanisms, as well as by observing the influence of external environment to the organization and vice versa. All data presented in this paper was based on interviews, observation, and study the documents. Result of research  indicate that from the six variables in organizational diagnosis process development PIK R/M in Pati Regency just found one of the variables as a whole it has been going well, namely on variable rewards. Five other variables found to have problems, namely the purpose, structure, relationships, leadership and helpful mechanisms. The influence of the external environment of the Organization, and the Organization was also able to influence the external environment. A type of intervention that allows for applied was Human Process Intervension approach, through the Coaching with GROW (Goal, Reality, Options, Warm-Up) as model as created by Graham Alexander dan  Sir John Whitmore. Which these interventions focus on human beings within the Organization, and the process of how they are in achieving the objectives of the organization.